Upaya Penguatan Pendidikan Agama Islam dalam Meningkatkan Kualitas Karakter Siswa di SMPN 2 Sultan Daulat - Salamah Salamah (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Strengthening character education through Islamic Religious Education (IRE) has become a strategic priority in improving the quality of students amid the growing challenges of moral degradation in school environments. However, the implementation of integrated Islamic Religious Education reinforcement within school management systems has received limited scholarly attention, particularly at the junior secondary school level. This study aims to analyze the efforts to strengthen Islamic Religious Education in improving students' character quality at SMPN 2 Sultan Daulat, Indonesia. A qualitative approach was employed, with data collected through in-depth interviews, observations, and document analysis. The data were analyzed descriptively using the processes of data reduction, data display, and conclusion drawing. The findings reveal that the reinforcement of Islamic Religious Education was implemented through four major stages: program planning, assignment of an assessment team, program implementation, and continuous monitoring and evaluation. The implementation of the program significantly enhanced students' character quality, as reflected in improvements in religiosity, personal character, discipline, and compliance with school regulations. Furthermore, the proportion of students meeting the school's character standards increased from 81% prior to the program to 93% following its implementation. This study contributes to the literature by proposing a school-based Islamic Religious Education reinforcement model that integrates religious habituation, character assessment, and collaborative school management as an effective strategy for fostering sustainable student character development. [Penguatan pendidikan karakter melalui Pendidikan Agama Islam (PAI) menjadi salah satu isu strategis dalam meningkatkan kualitas peserta didik di tengah berbagai tantangan degradasi moral di lingkungan sekolah. Namun, implementasi penguatan PAI yang terintegrasi dalam sistem pengelolaan sekolah masih belum banyak dikaji secara mendalam, khususnya pada jenjang sekolah menengah pertama. Penelitian ini bertujuan untuk menganalisis upaya penguatan Pendidikan Agama Islam dalam meningkatkan kualitas karakter siswa di SMPN 2 Sultan Daulat. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Analisis data dilakukan secara deskriptif melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penguatan Pendidikan Agama Islam dilaksanakan melalui empat tahapan utama, yaitu perencanaan program, pembagian tugas tim penilai, pelaksanaan program, serta pengendalian dan evaluasi secara berkelanjutan. Implementasi program tersebut terbukti mampu meningkatkan kualitas karakter siswa, yang ditunjukkan oleh perubahan positif pada aspek religiusitas, karakter, kedisiplinan, dan kepatuhan terhadap tata tertib sekolah. Selain itu, terjadi peningkatan capaian karakter siswa dari 81% sebelum program diterapkan menjadi 93% setelah implementasi program. Penelitian ini berkontribusi dalam menawarkan model penguatan Pendidikan Agama Islam berbasis manajemen sekolah yang mengintegrasikan pembiasaan keagamaan, sistem evaluasi karakter, dan kolaborasi seluruh warga sekolah sebagai strategi efektif dalam membentuk karakter peserta didik]